Incidence of the mechanized sowing speed in irrigated rice (2017)
This paper presents some experimental results to determine the incidence of mechanized sowing speed in the development and growth of rice in El Espinal-Tolima. Using a completely randomized design and a seed density of 104.5 ± 3.3 kg/ha, plots were sown in three replicates at 3.31 ± 0.05 km/h, 5.13 ± 0.18 Km/h, and 6.98 ± 0.24 km/h. Plant population, plant weight, dry matter, moisture content, and yield showed statistically significant differences with respect to sowing speed. This research found that the sowing speed has a proportional relationship with: a) the percentage of plants grouped in their roots, b) the number of non-productive tillers, c) the fuel consumed rate, d) uncovered seed, e) effective field capacity. The sowing speed of 5.13 ± 0.18 km/h was achieved by plants with a higher number of panicles per m2 and yield: this is optimal.